Arctic National Wildlife Refuge (ANWR): Controversies for the 109th Congress - Corn, M. Lynne; Gelb, Bernard A.; Baldwin, Pamela (Library of Congress. Congressional Research Service., 2005)
This report provides information on Arctic National Wildlife Refuge (ANWR) and its Controversies for the 109th Congress.